2009
DOI: 10.1007/978-3-642-04346-8_34
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Google to Ask-a-Librarian Service for Answering Factual and Topical Questions

Abstract: Abstract. This paper evaluates to which extent Google retrieved correct answers as responses to queries inferred from factual and topical requests in a digital Ask-a-Librarian service. 100 factual and 100 topical questions were picked from a digital reference service run by public libraries. The queries inferred simulated average Web queries. The top 10 retrieval results were observed for the answer. The inspection was stopped when the first correct answer was identified. Google retrieved correct answers to 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…Findings show that just under half of origins are useful (43.7%) and over three-quarters of trails have useful pages (82.8%). This shows that the likelihood of finding a useful page via navigation is high, a finding supported by previous work on post-query search behavior [23]. This may also be because origins are search results, typically the starting points for a task, and hence have rapid click-though [17][21].…”
Section: Different Metricssupporting
confidence: 73%
“…Findings show that just under half of origins are useful (43.7%) and over three-quarters of trails have useful pages (82.8%). This shows that the likelihood of finding a useful page via navigation is high, a finding supported by previous work on post-query search behavior [23]. This may also be because origins are search results, typically the starting points for a task, and hence have rapid click-though [17][21].…”
Section: Different Metricssupporting
confidence: 73%
“…Borrowing books, fiction in particular is likely to be affected differently compared to reference services by the internet. For example, although Vakkari and Taneli (2009) have shown that a digital Ask-a-Librarian service run by public libraries outperforms Google in answering factual and topical questions, the popularity of Ask-a-Librarian sites in the US is relatively low (OCLC, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Online question answering sites in particular have been the object of increasing evaluation. Some of the studies have also included public library reference services (Harper et al , 2008; Shachaf, 2009; Vakkari and Taneli, 2009).…”
Section: Related Researchmentioning
confidence: 99%
“…Vakkari and Taneli (2009) compared the extent to which Google retrieved correct answers to queries inferred from factual and topical requests in a digital Ask‐a‐Librarian service. These queries simulated typical web queries.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation